Microalbuminuria in Patients with Hypertension Visiting Tertiary Care Centre, Western Nepal - Twayana, Yuresh; Pokhrel, Buddhi Raj; Tamang, Binaya; Jha, Amit Chandra; Gautam, Narayan; Jayan, Archana; Dubey, Raju Kumar; Dhakal, Pushpa Raj (Journal of Nepal Health Research Council, 2021)
Background: Renal complications of hypertension are associated with high morbidity and mortality. Prediction of such complications at the earliest is of utmost importance. We aimed to assess the prevalence of microalbuminuria in hypertensive patients. Methods: A total of 130 clinically diagnosed hypertensive patients were enrolled in the study. Biochemical parameters that included serum creatinine, urinary albumin, and urinary creatinine were measured using standard methods. Albumin Creatinine ratio and estimated glomerular filtration rate were calculated. Albumin Creatinine ratio values between 30-300 mg/g were considered as microalbuminuria. Statistical analysis was performed on 120 samples after excluding frank proteinuria. Results: The prevalence of microalbuminuria in hypertensive patients was 19.16%. Mean ranks of systolic blood pressure, pulse pressure, and serum creatinine levels were significantly higher in hypertensive patients with microalbuminuria. Mean estimated glomerular filtration rate was significantly low in hypertensive patients with microalbuminuria. Older age and increased duration as well as severity of hypertension were not associated with a higher prevalence of microalbuminuria. Conclusions: The prevalence of microalbuminuria was high in hypertensive patients. Serum creatinine and estimated glomerular filtration rate were significantly altered in patients with microalbuminuria. Early screening of microalbuminuria in such patients might help prevent renal complications. Keywords: ACR; creatinine; eGFR; hypertension; microalbuminuria